Fiscal sustainability in the presence of structural breaks: Does overconfidence on resource exports hurt government's ability to finance debt? Evidence from Nigeria - Aliyu Alhaji Jibrilla (Cogent Economics & Finance, 2016)
The sustainability of the Nigerian fiscal deficit along with the role of the dynamics of government revenues and spending in adjusting the size of the deficit is examined using annual data from 1961 to 2014. After allowing for structural breaks, the study finds evidence of a cointegration relation between the government revenues and spending. The results did not indicate the presence of asymmetries in either the threshold autoregression or momentum threshold autoregression specifications of the country's budgetary adjustment process. Interestingly, the size of the long run slope parameter appears to be significantly less than one, thus offering support for the soft budget strategy, which also suggests that the government might face difficulties in financing its debts in the long run. Lastly, the short run and long run Granger causality results, while providing evidence in support of the fiscal synchronization hypothesis, also raise some important issues, particularly on the strength of budget deficit sustainability in the country.
Keywords: C1; E62; H6; Q32; 330; revenues; expenditures; oil price volatility; structural breaks; budget deficit sustainability; causality; error correction